A multimodal physiological-psychological data-driven study on differentiation in miners’ job burnout and risk preferences - Tian, Fangyuan; Qiu, Weishuai; Li, Hongxia; Zhao, Ziyi (Frontiers in Psychology, 2024)
Background Existing research indicates that the personality traits of miners influence their emotional regulation strategies, and these strategies in turn affect their performance in work fatigue. However, whether there is an intermediary or moderating role among these factors remains unclear. Additionally, while some studies suggest an increased likelihood of unsafe behavior among miners following fatigue, physiological data concerning their cognition remains incomplete and requires further exploration. This study aims to explore the mediating and moderating effects of emotional regulation strategies among miners regarding their personality traits and work fatigue, and to expand understanding of the cognitive and physiological data related to miners’ risk decision-making following fatigue. Method Fifty adult miners (Mage = 25, aged 18–40, 100% male) were selected as participants. Emotional regulation tendency, significant levels of personality traits based on the Big Five Personality Traits questionnaire, and the three-dimensional levels of work fatigue were measured using emotional regulation strategy scale, Big Five Personality Traits questionnaire, and work fatigue scale, respectively. The eye–brain consistency hypothesis posits that eye movement trajectories and fixation points reflect the brain’s cognitive processes and focus. Therefore, combining eye-tracking experiments, miners’ preferences in risk decision-making were further measured. Results Expressive suppression strategies mediated between conscientiousness and depersonalization; expressive suppression strategies moderated between agreeableness and emotional exhaustion. In eye-tracking physiological experiments, significant differences were found in eye movement data among miners with varying levels of emotional exhaustion. Conclusion Preferences in emotional regulation strategies play mediating and moderating roles between miners’ Big Five Personality Traits and work fatigue. The levels and dimensions of work fatigue are influenced not only by personality traits but also by individual tendencies in emotional regulation strategies, which significantly affect performance in risk decision-making. The findings of this study can further enrich theories related to work fatigue among miners and provide insights for personalized safety management in mining.